Bioenzymatic detoxification of mycotoxins - Liu, Mengyu; Zhang, Xue; Luan, Haoni; Zhang, Yue; Xu, Wei; Feng, Wei; Song, Peng (Frontiers in Microbiology, 2024)
Mycotoxins are secondary metabolites produced during the growth, storage and transportation of crops contaminated by fungi and are physiologically toxic to humans and animals. Aflatoxin, zearalenone, deoxynivalenol, ochratoxin, patulin and fumonisin are the most common mycotoxins and can cause liver and nervous system damage, immune system suppression, and produce carcinogenic effects in humans and animals that have consumed contaminated food. Physical, chemical and biological methods are generally used to detoxify mycotoxins. Although physical methods, such as heat treatment, irradiation and adsorption, are fast and simple, they have associated problems including incomplete detoxification, limited applicability, and cause changes in food characteristics (e.g., nutritive value, organoleptic properties, and palatability). Chemical detoxification methods, such as ammonification, ozonation and peroxidation, pollute the environment and produce food safety risks. In contrast, bioenzymatic methods are advantageous as they achieve selective detoxification and are environmentally friendly and reusable; thus, these methods are the most promising options for the detoxification of mycotoxins. This paper reviews recent research progress on common mycotoxins and the enzymatic principles and mechanisms for their detoxification, analyses the toxicity of the degradation products and describes the challenges faced by researchers in carrying out enzymatic detoxification. In addition, the application of enzymatic detoxification in food and feed is discussed and future directions for the development of enzymatic detoxification methods are proposed for future in-depth study of enzymatic detoxification methods.